Analisis Putusan Terhadap Pemutusan Hubungan Kerja Yang Putus Karena Usia Pensiun (Studi Putusan Nomor: 232/Pdt-Sus-PHI/2024/PN MDN) - Pratama, Naufal Arif; Nurhayati, Siti (Jurnal Multidisiplin Dehasen (MUDE), 2025)
From various court rulings, judges are often faced with differences of opinion between workers and companies regarding the compensation that should be given in termination of employment due to retirement age. The number of cases shows that there is dissatisfaction with the amount of compensation provided by the company, so workers file a lawsuit in court. In such a situation, judges have an important role in upholding justice and delivering a balanced verdict between workers' rights and company obligations. In this study, it discusses the legal protection for workers who experience termination due to retirement age and the analysis of decisions on termination of employment due to retirement age based on Decision Number: 232/Pdt-Sus-PHI/2024/PN Mdn). The type of research used is normative juridical research, which is research that refers to legal norms contained in laws and regulations, court decisions and legal norms that exist in society. Decision Number: 232/Pdt-Sus-PHI/2024/PN Mdn, that Article 157 Paragraph (1) of Law Number 13 of 2003 concerning Manpower which was later amended by Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into law, states that the wage component used as the basis for the calculation of severance pay and service award money consists of basic wages and fixed allowances given to workers/laborers and their families.